2022
DOI: 10.3390/chemosensors10020073
|View full text |Cite
|
Sign up to set email alerts
|

Solid Fluorescence pH Sensors Based on 1,8-Naphthalimide Copolymers Synthesized by UV Curing

Abstract: Novel water-swollen photo-crosslinked membranes were obtained by copolymerization of the N-vinylpyrrolidone, butyl acrylate and ethyl methacrylate monomers functionalized with naphthalimide groups, as pH sensitive fluorescence probes. For that purpose, two monomers with pending naphthalimide groups anchored to ethyl methacrylate through alkyl chains with different length, were previously synthesized. The membranes were characterized using different techniques. The pH dependence of absorbance and the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, this can shift depending on the derivative and the solvent, as shown in Table 1. Naphthalimide fluorescence intensity is highly responsive to changes in pH [135]. This occurs due to a photoinduced electron transfer (PET) effect within the napthalamine structure.…”
Section: Acceptors: Naphthalimide and Quinolinementioning
confidence: 99%
See 2 more Smart Citations
“…However, this can shift depending on the derivative and the solvent, as shown in Table 1. Naphthalimide fluorescence intensity is highly responsive to changes in pH [135]. This occurs due to a photoinduced electron transfer (PET) effect within the napthalamine structure.…”
Section: Acceptors: Naphthalimide and Quinolinementioning
confidence: 99%
“…The emission maximum of 8-HQ occurs at 467 nm, and a 5.5-fold fluorescence enhancement was observed upon the introduction of formaldehyde. Liu et al also explored the PET process using DFT calculations, which showed that in the absence of formaldehyde, the energy Naphthalimide fluorescence intensity is highly responsive to changes in pH [135]. This occurs due to a photoinduced electron transfer (PET) effect within the napthalamine structure.…”
Section: Acceptors: Naphthalimide and Quinolinementioning
confidence: 99%
See 1 more Smart Citation
“…The ability to self-organize, accompanied by high thermal stability, and chemical and oxidation resistance, render the naphthalimides good acceptor-donor materials [ 19 , 20 , 21 , 22 , 23 , 24 ]. In addition, the 1,8-naphthalimide derivatives were also used as dyes for cell imaging and as probes or sensors [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among different fluorescent chemosensors, naphthalimide derivatives are attracting much attention due to their excellent stability, photophysical, thermal, electrochemical and electroluminescence properties, which can be modulated by introduction of different substituents at the 4th position of the naphthalimide ring. Despite the many naphthalimides synthesized, the design of new fluorescent sensors which exhibit high selectivity and sensitivity fluorescence, lowtoxicity and stability are still challenging (Geraghty et al, 2021;Gudeika, 2020;Lee, 2016;Li et al, 2012;Oshchepkov et al, 2021;Pablos et al, 2022;Poddar et al, 2019;Shaki et al, 2010;Tian et al, 2010;Zhang et al, 2019). This paper reports on the design and synthesis of novel PET based 1,8-naphthalimide fluorophore (1).…”
Section: Introductionmentioning
confidence: 99%